Exploration of Pectin – Utilizing Yeast From Soil of Bogor and Wleri Fruit Orchards - Fahrizal Hazra (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2011)
There is a high demand on pectin–utilizing yeasts for industrial, agricultural and environmental purposes. Further exploration of yeast from various sources are important to enrich yeast culture collections. Nine yeast strains were isolated from various soil sources sampled based on biological sampling in Bogor and Central Java. Enriched media containing pectin as carbon sources was employed for isolation of the yeast. The isolated yeast were identified according to the methods described in monographs by Kreger – Van Rij (1984), Barnett et.al (2000), Guilliermond and Tanner (2006) . The strains isolated were taxonomically separated into 3 groups. Group I contains 3 strains, and this group is closely related to Candida tropicalis. Group II contains 4 strains, and this group is included in this genus Rhodotorula. Group III contain 2 strains, and this group is closely related to Williopsis saturnus, which is a synonym of Hansenula saturnus. Pectinolytic enzymes (Polygalacturonase) were produced by all of the tested strains. Polygalacturonase was produced as high as 1.7 U.ml-1 by strain no. 111 of group I, 1.7 U.ml-1 by strains no. 123 of group II, and 1.0 U.ml-1 by strain no. 211 of group III.Key words : yeast, pectin, polygalacturonase